(untitled) (Malay Literature, 2020)
This paper will analyse critically the arguments given by al-Raniri in his Fathul Mubin ala al-Mulhidin. Al-Raniri wrote Fathul Mubin after returning to Ranir in Gujerat. From the context of the text it is clear that al-Raniri had written it after he lost in a debate with Shaykh Saiful Rijal before Sultanah afiatuddin Shah, who was then the Sultanah of Acheh after the death of Sultan Iskandar Thani (d.1646). Al-Raniri had criticized the views of the wujudiyyah whom he labelled mulhidah (heretical) based upon his readings of several books written by Shaykh Hamzah Fansuri and Shaykh Shamsuddin Sumatrani (d.1630). Fathul Mubin is one a text often forgotten when discussing the conflict between the Sufi teachings of al-Raniri and those before him. Researchers are tend to view his other works concerning this debate and conflict. Recent research into Malay manuscripts has alerted us to the existence of this text and as a result we are able to study the views of al-Raniri in more detail than in his other oftenviewed book, Jawahiral-Ulum fi Kasfhul Ma’lum.The findings of this research show us that we have to look back at the facts as stated in Fathul Mubin. Understanding the issue objectively enables us to see the facts and arguments in a clear and systematic light. Keywords: al-Raniri, wujudiyyah, Malay manuscripts, history, sufism, tasawwuf, Malay world